1988
DOI: 10.1071/bi9880157
|View full text |Cite
|
Sign up to set email alerts
|

Polyploid Abnormalities in Day 3 and Day 5 Merino Sheep Embryos

Abstract: The chromosome complement was assessed in Merino sheep embryos collected at 3 and 5 days after the onset of oestrus. Donor ewe treatments were: untreated, or immunized against androstenedione (day 3); and untreated, or treated with follicle-stimulating hormone (FSH), or treated with FSH plus immunization against androstenedione (day 5). No significant differences in the frequency of chromosomally abnormal embryos between treatment groups within each age group were observed, so the data have been combined.Euplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…After measurement, all embryos were cultured in a solution of colchicine and processed for chromosome analysis (Murray et al, 1985(Murray et al, , 1986a). The chromosome data from the day 2 embryos have been reported separately (Murray et al, 1988).…”
Section: Measurement Of Embryos and Blastocystsmentioning
confidence: 99%
“…After measurement, all embryos were cultured in a solution of colchicine and processed for chromosome analysis (Murray et al, 1985(Murray et al, , 1986a). The chromosome data from the day 2 embryos have been reported separately (Murray et al, 1988).…”
Section: Measurement Of Embryos and Blastocystsmentioning
confidence: 99%
“…Chromosomal imbalances are considered a significant cause of embryonic death in mammals. Studies on preimplantation stages showed chromosomal anomalies in 2% of mice (Maudlin and Fraser, 1978) and hamster (Sengoku and Dukelow, 1988), in 10% of pig (Mc-Feely, 1967), in 6-11% of sheep (Long and Williams, 1980;Murray et al, 1988;Boland et al, 1986), and i n 20% of human embryos (Angel1 et al, 1983;. In the rabbit, up to 17% of preimplantation embryos showed an abnormal chromosomal composition (for references, see Discussion).…”
Section: Introductionmentioning
confidence: 99%